Evaluation of the Antibacterial Activity of Various Spice Extracts Commonly Consumed in the Libyan Diet - Nadia Salem Alrawaiq; Huda Salem Alrawiq; Nasser alrawiq; Ayah Abusaif; Halima Khair (African Journal of Advanced Pure and Applied Sciences, 2025)
Spices have long been used in cooking to improve the taste of food. This study investigated the antibacterial properties of six different spices, using both water-based and alcohol-based extracts. The spices examined were black pepper, red pepper, cardamom, turmeric, caraway, and coriander seeds. The current study tested these extracts against three types of bacteria: Staphylococcus aureus (a Gram-positive bacterium), as well as Escherichia coli and Pseudomonas aeruginosa (both Gram-negative). The results showed that ethanol (alcohol) extracts of the spices significantly reduced the growth of all three bacteria tested (p < 0.05). When ranking the antibacterial effectiveness of the six spices, coriander was the most effective, followed by turmeric, caraway, black pepper, cardamom, and finally red pepper. Among the water-based extracts, caraway stood out for its particularly strong antibacterial action. Interestingly, red pepper extract was especially potent against P. aeruginosa, while extracts of cardamom, black pepper, and turmeric did not inhibit bacterial growth in some cases. Generally, the spices showing the best antibacterial effects were coriander, caraway, red pepper, black pepper, turmeric, and cardamom. Notably, there was no significant difference in antibacterial effectiveness between the two types of extracts (p > 0.05). Overall, the findings suggest that these six spices have the potential to combat bacteria effectively. Of the bacteria tested, P. aeruginosa was the most sensitive to the spice extracts, followed by E. coli, whereas S. aureus was the most resistant. These results indicate that these common spices could offer a safe and natural alternative for treating bacterial infections in the future.